The river returns : an environmental history of the Bow - Armstrong, Christopher (McGill-Queen's University Press, 2009)
"Rivers have been studied from many perspectives, but too often the relationship between nature and people, between rivers and the cultures that have grown up beside them, have been separated. The River Returns illuminates the ways in which humans, both inadvertently and consciously, have interacted with nature to create Alberta's legendary Bow River."--BOOK JACKET.